Investigation of immunosuppressive treatment compliance, dyspnea, anxiety, and depression levels in lung transplant recipients: online interview - Bulbuloglu, Semra; Sayim, Halil Ibrahim (Frontiers in Psychology, 2024)
Introduction Following lung transplantation (LTx), it is important for recipients to comply with immunosuppressive treatment and cope with related problems. In the post-LTx period, the course of dyspnea and psychological problems it causes in case of progression are not known. Depression and anxiety may develop in recipients after LTx. However, the relationship between this situation and treatment compliance and dyspnea is uncertain. Objective The aim of this study was to investigate dyspnea, anxiety, and depression levels of recipients following LTx and their immunosuppressive treatment compliance. Method The study was planned as a descriptive, correlational, and cross-sectional study. Data were collected on various social media platforms via an online interview, and 65 LTx recipients were included in the sample (n = 65). A Participant Information Form, the Modified Borg Scale, the Beck Anxiety Inventory, the Beck Depression Inventory, and the Immunosuppressive Drug Compliance Scale were employed to collect data. The collected data were analyzed using descriptive statistics, the Mann–Whitney U test, and the Kruskal-Wallis test. Results The mean age of the participants was found to be 52.60 ± 9.44 years, and 56.9% were male. Forty percent of the participants were dependent on oxygen support, and 32.2% had hypertension. Their dyspnea levels were mild, anxiety levels were moderate, depression levels were high, and immunosuppressive treatment compliance levels were slightly above-average. According to the correlation analysis results, dyspnea was associated with anxiety and depression (p < 0.05). As depression increased, immunosuppressive treatment compliance decreased, and the correlation between the two variables was statistically significant (p < 0.05). Conclusion In this study, as the severity of dyspnea experienced by LTRs increased, the severity of their anxiety and depression also increased. Additionally, there was an inverse correlation between depression and immunosuppressive treatment compliance. LTRs demonstrated insufficient adherence to their immunosuppressive drug regimens, which is very significant in terms of graft survivability. These results suggest that LTRs should be closely monitored at home.